Monitoring cameras for violations in the use of personal protective equipment - Maulana Rasiddin, Muhammad; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Work Safety is an activity and effort to create a safe work environment, preventing all forms of accidents. To implement safe actions for workers, Personal Protective Equipment (PPE) is needed for workers to protect someone in doing their work. This Personal Protective Equipment (PPE) monitoring system begins by turning on the system by flowing the power supply to the system. Then the system is set via an access point via WiFi to be able to set the system on the microcontroller GUI. Then by selecting to activate